Kepolosan Tokoh Paddington dalam Film Paddington (2014) - Alviannisa, Adisty Tria (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research is motivated by the view that literary works, including children's films, serve not only as entertainment but also as a means of moral learning that plays an essential role in shaping children's character. The film Paddington (2014) was chosen because it features an innocent main character who can represent moral values ​​through simple actions and dialogue. The purpose of this study is to describe how the main character's innocence is depicted in the film and how these moral values can serve as a learning medium for children. This study uses a qualitative descriptive approach with content analysis. Data were obtained through observations of scenes, dialogues, and the main character's actions that demonstrate innocence and the moral values ​​contained therein. The results show that Paddington's innocence manifests in honesty, politeness, trust, and a high level of curiosity, though this often leads to misunderstandings or chaos. This innocence serves as a medium for conveying moral values ​​such as responsibility, empathy, and learning from mistakes. The implications of this study indicate that children's films can be an effective means of character education if studied and accompanied by an understanding of the moral values ​​contained therein.